IMPLEMENTASI ALAT PERAGA KUBUS SATUAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS 5 DI MI MA’ARIF KLIWONAN - Ida Fitri Nahdiyati; Maryono Maryono; Salis Irvan Fuadi (Pusat Riset dan Inovasi Nasional, 2023)
Writing this thesis aims: 1) To find out student learning outcomes in class volume cube material; 2) To determine the effect of unit cube teaching aids on student learning outcomes; 3) To find out whether there are differences in the learning outcomes of class students who use unit cube teaching aids with classes that do not use unit cubes. This thesis uses a quantitative method with the type of quasi-experimental research. The samples used are two classes, namely class 5 A and class 5 B. Data collection techniques use observation, documentation, interviews and tests. This study used instrument test analysis Then data analysis techniques were used using tests and hypothesis testing. The results showed that: 1) There were differences in grade 5 student learning outcomes between classes that used unit cube teaching aids and those that did not use unit cube teaching aids with the calculation results t test obtained tcount 2.374 and ttable 1.672 so the result is tcount > ttable meaning H1 is accepted and H0 is rejected. 2) There is an increase in student learning outcomes after using unit cube teaching aids based on hypothesis testing with the control class results obtained at 0.61. It can be concluded that the improvement in control class learning outcomes is in the moderate category. While the n-gain test for the experimental class obtained results of 0.70, it was concluded that the increase in learning outcomes for the experimental class was in the high category.